Effective use of Metacognition to Address Implicita Problems - Fatma, Ishrat (Journal of Advanced Research in English & Education, 2023)
Metacognition or thinking critically is a scholarly skill boosting the in-depth cognitive qualities of students which requires sincere instructions and continuous practice. Teachers or faculty members can develop students’ skills of critical thinking by adopting various methodologies as well as education strategies to enhance the engagement of the learners to speed up their process of learning and help them to assimilate into their pragmatic approach towards solving the challenges of life, rather than emphasizing on mere rote learning and making them memorize the facts and information. A well-organized teaching plan with project-based learning, group activities, and question-based techniques can trigger the critical thinking of the students, motivating them to leave behind the comfort zone of the supplied information and to put them on fire to see the concept or situation from an entirely new perspective of their own. Faculty can encourage students to think about the information they know, which in turn will prove a boon in sharpening their life skills with a more authentic critical approach to handling the problems of the real world. How to cite this article:  Fatma I. Effective use of Metacognition to Address Implicita Problems. J Adv Res Eng & Edu 2022; 7(4): 4-9. DOI: https://doi.org/10.24321/2456.4370.202214